Towards production of novel catalyst powders from supported size-selected clusters by multilayer deposition and dicing. (18th July 2017) - Jian, Nan; Bauer, Karl; Palmer, Richard E
Abstract: A multilayer deposition method has been developed with the potential to capture and process atomic clusters generated by a high flux cluster beam source. In this deposition mode a series of sandwich structures each consisting of three layers—a carbon support layer, cluster layer and polymer release layer—is sequentially deposited to form a stack of isolated cluster layers, as confirmed by through-focal aberration-corrected HAADF STEM analysis. The stack can then be diced into small pieces by a mechanical saw. The diced pieces are immersed in solvent to dissolve the polymer release layer and form small platelets of supported clusters.